Evaluation of Women’s Contribution to Agricultural Development in Yobe State, Nigeria - Sanusi, S. O.; Madaki, M. J. (European Journal of Applied Sciences, 2022)
The study evaluated women’s contribution to agricultural development and the impact of Boko haram conflicts in Yobe State, Nigeria. Primary data collected with the aid of a well-structured questionnaire was used to elucidate responses from women farmers. About 351 women farmers were interviewed for the stud. This comprised of one-hundred and sixty-two (160) non-beneficiaries and one hundred and ninety-one (191) programme beneficiaries respectively. Descriptive Statistics and Propensity Scoring Matching were utilized for data analysis. From the results, the average age for non-beneficiaries, beneficiaries, and pooled data was 49.50, 47.60, and 48.55, respectively. The average household size was 6 individuals per household. Also, Non-beneficiaries, beneficiaries, and pooled data had total yearly incomes of ₦261,716.00 ($629. 34), N285,595.90 ($686.76), and N273,655.95 ($658.05) respectively. FADAMA program was the major program women farmers benefited from in the study area. The result of Propensity score matching revealed that the value of average treatment effects for nearest neighbour, radius, kernel, and stratification were 0.273, 0.145, 0.163, and 0.183 respectively and were statistically significant at a 1% probability level. This suggests that the Boko haram conflict had a significant impact on the participation of women in agriculture. Based on the findings of the research, the study concluded that women contribute immensely to agricultural development and nutrition in the area. However, Boko harm crisis had an impact on womens’ involvement in agriculture. The study recommended more measures be put in place by the state government to encourage women's participation in agriculture as efforts are in course to curb the activities of Boko haram in the region.